«WEST – EAST» OPPOSITION IN RUSSIAN LITERATURE AND PHILOSOPHY OF 1830–1850S: : SEARCH FOR CIVILIZATIONAL IDENTITY - F. Bekmetov, Rinat; Rami, Ilsever; Sh. Yunusov , Ildar; N. Boldyreva, Olga (Gênero & Direito, 2019)
The article is devoted to the problem of determining the basic parameters of the cultural and civilizational identity of the Russian national character (the “Russian soul”) on the basis of literature and philosophy of the 30–50s of the 19th century. This period was not chosen by chance: in it, with the greatest strength and clarity, the leading trends in the development of Russian social (socio-philosophical) thought were identified, which had a direct and indirect influence on the literary process of the 19th century. In this transitional era, for certain reasons, objective conditions were created for the development of cornerstone ideological programs that became the subject of intellectual polemics, sometimes sharp and fierce, in subsequent times and which have not lost their relevance until now, as can be judged by modern book production, developing at the philosophical level, the most important questions of the future of Russia as a civilizational “mainland”, and on those very topical discussions that are conducted in the media space (television, no). One of the vivid exponents of this dispute was Petr Chaadaev, whose views on the cultural and civilizational identity of Russia were distinguished by a deep originality, which was in contrast with the official world outlook trends of the era. In the 1830–1850s, a discussion arose between “Slavophiles” and “Westerners”, which was also conducted on the pages of fiction. Due to this, a deprived of monolithic, rather contradictory picture of the perception of the West and the East as civilizational landmarks of the “Russian soul” has developed in the Russian consciousness. So, the East acted not only as a standard of high and refined culture, a role model, but also as a synonym for ignorance and inertness – all that is recorded in the capacious word meaning “Asian”. In the same way, the West was both a model of enlightenment and technocratic progress, and a kind of form of spiritual dependence associated with the decay and decay of the national. Such judgments were characteristic not only of the Russian society of the 1830–1850ss. In one form or another, they met in previous periods of Russian history, and in those countries of the world where the modernization process was coupled with the westernization of the cultural environment.